Analisis Wakaf Saham Perspektif Fukaha Klasik dan Kontemporer - Waluya, Atep Hendang (STAI Al Musaddadiyah Garut, 2025)
The implementation of stock waqf in Indonesia is relatively new and holds enormous potential. Despite this enormous potential, only a small portion has been achieved, and one factor contributing to this limited potential is the low level of public literacy regarding stock waqf. This paper aims to examine and analyze the views of classical and contemporary jurists regarding stock waqf. Most contemporary jurists view stock waqf as a takhrīj of waqf mushā, or collective property waqf, because shares are collectively owned. Classical fukaha from the Shafi'i and Hanbali schools and strengthened by Wahbah al-Zuhāylī, Ibn 'Abdullāh al-Maymān, Muḥammad Ṣāliḥ, Aḥmad bin Muḥammad al-Khalīl¸ Ghulām Muṣṭafā Nukhbah, al-Dubyān, al-Ṭayyār, al-Muṭlaq, al-Mūsā, and Khālid bin 'Alī al-Mushayqiḥ, they all argue that waqf of collective property, whether it can be shared or not, is absolutely valid and permissible to donate. The reason that strengthens the permissibility of waqf of collective property is the existence of a text that allows waqf of collective property and what the goal of waqf, whether with collective property or not, can be achieved. Therefore, share waqf which is the takhrīj of collective property waqf, according to the majority of jurists, is permissible and valid. Keyword: Fiqh Contemporary; Stock; Waqf.